Biomechanical Nasal Anatomy Applied to Open Preservation Rhinoplasty - Goksel, Abdulkadir; Saban, Yves; Tran, Khanh Ngoc (Facial Plastic Surgery, 2021)
Preservation rhinoplasty is a new way to reshape the nose by preserving the dorsum, nasal ligaments, soft tissue envelope, and muscles. This new concept provides the opportunity to achieve a more natural aesthetic and functional result. To achieve a good aesthetic and functional outcome while maintaining surgical safety, knowledge of the relevant anatomy is key. This is especially true for the preservation rhinoplasty technique, where a firm grasp of the anatomy of the nasal soft tissue and bony–cartilaginous framework is critical. The preservation technique is made more accessible by the open approach, which provides an opportunity for the deformity to be clearly visualized from the tip of the nose and the dorsum. Furthermore, tip plasty is easier to perform under direct vision, which is an advantage of the open approach. The goal of this article is therefore to make clear all the important anatomical structures and their relevance to the surgical steps taken when performing the open preservation rhinoplasty technique.
Keywords: rhinoplasty; preservation rhinoplasty; nose anatomy; open rhinoplasty; piezosurgery